A COMPREHENSIVE SYNTHESIS OF VIRTUAL MEMORY INNOVATIONS AND CHALLENGES - Hamza Qureshi; Muhammad Ali Hassan; Muhammad Suleman Javed; Muhammad Azam; Mubasher H Malik; Ammad Hussain (Spectrum of Engineering Sciences, 2025)
Virtual memory is a cornerstone of modern computing, providing an abstraction layer between physical memory and software applications. This paper offers a comprehensive overview of the evolution of virtual memory techniques, from early approaches such as Ad Hoc and Code-and-Fix to contemporary innovations like AI-driven memory management and Unified Virtual Memory (UVM). We explore key advancements, including Translation Lookaside Buffers (TLB), non-volatile memory (NVM), and memory deduplication, as well as the emerging challenges in ensuring security, performance, and real-time deterministic behavior across various computing environments. Special attention is given to the impact of virtualization in cloud systems and heterogeneous architectures, alongside the growing demands of modern workloads. The paper also discusses cutting-edge techniques like disaggregated memory architectures and quantum-inspired memory allocation, which promise to reshape the future of virtual memory management. Despite these advancements, trade-offs between performance, security, and scalability persist, requiring context-aware solutions tailored to specific system requirements. By synthesizing past, present, and future developments, this paper provides a holistic perspective on the dynamic field of virtual memory and its pivotal role in shaping the next generation of computing systems.